2017
DOI: 10.1039/c7nr03663a
|View full text |Cite
|
Sign up to set email alerts
|

Phase formation of nanolaminated Mo2AuC and Mo2(Au1−xGax)2C by a substitutional reaction within Au-capped Mo2GaC and Mo2Ga2C thin films

Abstract: Au-containing nanolaminated carbides MoAuC and Mo(AuGa)C were synthesized by a thermally induced substitutional reaction in MoGaC and MoGaC, respectively. The Au substitution of the Ga layers in the structures was observed using cross-sectional high-resolution scanning transmission electron microscopy. Expansion of c lattice parameters was also observed in the Au-containing phases compared to the original phases. Energy dispersive spectroscopy detected residual Ga in Au-substituted layers of both phases with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…11 After annealing, the 000l diffraction peaks of the capped (Cr 0.5 Mn 0.5 ) 2 GaC phase are shifted to lower diffraction angles. This observation is similar to previously reported Ga substitution by Au in the Mo 2 GaC phase, 25 indicating the formation of Mo 2 AuC with an expansion in the c-axis (the [000l] direction). We therefore assign the shifted peaks to 000l diffraction peaks of the new nanolaminated phase, (Cr 0.5 Mn 0.5 ) 2 AuC, formed by substituting the Ga atoms in the A layers by Au atoms.…”
Section: All Article Content Except Where Otherwise Noted Is Licenssupporting
confidence: 81%
See 3 more Smart Citations
“…11 After annealing, the 000l diffraction peaks of the capped (Cr 0.5 Mn 0.5 ) 2 GaC phase are shifted to lower diffraction angles. This observation is similar to previously reported Ga substitution by Au in the Mo 2 GaC phase, 25 indicating the formation of Mo 2 AuC with an expansion in the c-axis (the [000l] direction). We therefore assign the shifted peaks to 000l diffraction peaks of the new nanolaminated phase, (Cr 0.5 Mn 0.5 ) 2 AuC, formed by substituting the Ga atoms in the A layers by Au atoms.…”
Section: All Article Content Except Where Otherwise Noted Is Licenssupporting
confidence: 81%
“…Substitution of Si, Al, and Ga by Au was observed using scanning transmission electron microscopy (STEM), where the chemical analysis showed the possibility of both partial substitution and full substitution. [23][24][25] Along with the discovery of a new A element and additional members of the MAX phase family, it was also shown that the Ti 3 Au 2 C 2 phase can further react with an Ir capping layer, forming yet another nanolaminated phase, Ti 3 IrC 2 . This points towards a fully reversible intercalation of Au in the MAX phase, with Au diffusing in and out of the A layer without any substantial change of the metal carbide, e.g., Ti 3 C 2 , layers.…”
Section: All Article Content Except Where Otherwise Noted Is Licensmentioning
confidence: 99%
See 2 more Smart Citations
“…These phases can also be exfoliated to form a recently established class of two-dimensional materials labelled MXene. [11][12][13][14][15][16] The introduction of Au in M n+1 AX n phases by hightemperature-induced exchange can be used for Ga-containing MAX phases (Mo 2 GaC and Mo 2 Ga 2 C 17,18 ) to synthesize Mo 2 AuC and Mo 2 (Au 1Àx Ga x ) 2 through an Au substitution reaction with Ga. 19 The question remains whether this mechanism can be generally applied to other M n+1 AX n phases, and beyond. We chose thin films of Ti 2 AlC and Ti 3 AlC 2 as model system to address this question.…”
mentioning
confidence: 99%